The Patterns and Environmental Factors of Diversity, Co-Occurrence Networks, and Assembly Processes of Protistan Communities in Bulk Soils of Forests - Bing Yang; Lin Wu; Zhisong Yang; Zhihe Zhang; Wanju Feng; Weichao Zheng; Chi Xu (Microorganisms, 2025)
Understanding the maintenance of soil protists within forest ecosystems is crucial for comprehending ecosystem responses to climate change. A comprehensive analysis of soil samples from the Fengtongzhai National Reserve in China, utilizing high-throughput sequencing and network analysis, indicates that topsoil protistan communities predominantly comprise consumers, parasites, and plant pathogens. The principal phyla identified include Stramenopiles, Alveolates, Rhizaria (SAR), Cercozoa, Apicomplexa, and Ciliophora, with Monocystis, Rhogostoma, Cercomonas, and Globisporangium as the most prevalent genera. Although α diversity metrics did not reveal significant differences across various forest types, β diversity demonstrated notable distinctions, primarily influenced by soil pH, organic carbon content, and moisture levels. Complex co-occurrence networks were particularly evident in deciduous broadleaved and evergreen broadleaved mixed forests. The stability of these networks was higher in plantation forests compared with natural forests, with no significant differences observed among the three natural forest types studied. This finding challenges the reliability of using soil protists as indicators for forest soil health assessments. Stochastic processes, especially ecological drift, play a significant role in shaping these communities. In conclusion, the findings suggest that the mechanisms underlying the enhanced stability of co-occurrence networks of soil protists in plantations require further investigation. Additionally, the specific responses of soil protists to forest type highlight the necessity of incorporating multidimensional indicators in the evaluation of forest soil health and the effectiveness of ecological restoration efforts.